Evaluación de diferentes programas de fertilización del cultivo de pimiento (Capsicum annum) en la zona de Puebloviejo, Provincia de Los Ríos - Orozco Zambrano, Francisco Eliseo (2015)
The cultivation of pepper (Capsicum annuum) is native to Mexico, Bolivia and Peru. In Ecuador approximately 1145 hectares are cultivated and in the province of Los Ríos 150 hectares. Within this species there are numerous varieties generated by differences in climate and soil conditions, among other factors. In greenhouse cultivation plant density is 20,000 to 25,000 plants / ha. In field reaches 60,000 plants/ ha. The objective of this research was to evaluate the effectiveness of the implementation of various programs of fertilization on yield and crop performance pepper, further economic analysis. The work was done in the land of Mr. Francisco Orozco Zambrano, located at Kilometer 38 of the Babahoyo-Puebloviejo route. Eight treatments were investigated with 3 replications. Sowing was done with pepper seed Marcato, in plots of 20 m2. The treatments were arranged in a completely randomized design blocks. Tukey's test was used for evaluation of means. At the end of the crop cycle was evaluated: plant height, days to flowering, days to harvest, fruit diameter, fruit length, number of fruits per plant, brightness of fruit, fruit weight and yield per hectare......